Adequacy of social minimums: Workfare, gender and poverty alleviation in welfare democracies - Kenneth Nelson (Luxembourg Income Study (LIS), 2008)
In the Western countries poverty has increased along with the resurgence of low-income targeting and the increased conditionality of social assistance. This paper provides new evidence on the relationship between social minimums and income adequacy by examining the extent to which social benefits distribute income at levels necessary to escape poverty. The empirical analyzes combine macro-level institutional data and micro-level income data for 17 industrialized welfare democracies. It is shown that the period 1990-1995 is characterized primarily by stagnation, whereas social assistance adequacy declined in the latter half of the nineties. In most countries, social assistance fails to provide income above the poverty threshold, something that makes it difficult to conceive benefits as just redistributive instruments.
Keywords: 330; Sozialstaat; Grundbedürfnisse; Mindestlohn; Aktivierende Arbeitsmarktpolitik; Öffentliche Sozialleistungen; Geschlechterdiskriminierung; Industrieländer